Subject (in) Trouble: Humans, Robots, and Legal Imagination - Oliveira, Ana (2020)
The legal conception and interpretation of the subject of law have long been challenged by different theoretical backgrounds: from the feminist critiques of the patriarchal nature of law and its subjects to the Marxist critiques of its capitalist ideological nature and the anti-racist critiques of its colonial nature. These perspectives are, in turn, challenged by anarchist, queer, and crip conceptions that, while compelling a critical return to the subject, the structure and the law also serve as an inspiration for arguments that deplete the structures and render them hostages of the sovereignty of the subject’ self-fiction. Identity Wars (a possible epithet for this political and epistemological battle to establish meaning through which power is exercised) have, for their part, been challenged by a renewed axiological consensus, here introduced by posthuman critical theory: species hierarchy and anthropocentric exceptionalism. As concepts and matter, questioning human exceptionalism has created new legal issues: from ecosexual weddings with the sea, the sun, or a horse; to human rights of animals; to granting legal personhood to nature; to human rights of machines, inter alia the right to (or not to) consent. Part of a wider movement on legal theory, which extends the notion of legal subjectivity to non-human agents, the subject is increasingly in trouble. From Science Fiction to hyperrealist materialism, this paper intends to signal some of the normative problems introduced, firstly, by the sovereignty of the subject’s self-fiction; and, secondly, by the anthropomorphization of high-tech robotics.